Effect of different legume seeds on life table parameters of cowpea weevil, Callosobruchus maculatus (F.) (Coleoptera: Chrysomelidae). (January 2021) - Bidar, Forough; Razmjou, Jabraeil; Golizadeh, Ali; Asghar Fathi, Seyed Ali; Ebadollahi, Asgar; Naseri, Bahram
Abstract: The cowpea weevil, Callosobruchus maculatus (F.) (Coleoptera: Chrysomelidae) is one of the most important storage pests of legume seeds. The effect of various legume species including chickpea ( Cicer arietinum L.) (cultivars Hashem and Mansour), cowpea ( Vigna unguiculata L.) (cultivars Mashhad and 1057), green gram ( Vigna radiata L.) (cultivar Parto), lentil ( Lens culinaris Medikus) (cultivar Bilehsavar) was studied on the life history and life table parameters of C. maculatus at 30 ± 1 °C, relative humidity of 65 ± 5% and complete darkness. The developmental time was longest on lentil and shortest on cowpea 1057. The fecundity (number of eggs laid per reproductive period) of the pest was the lowest on lentil. The longest oviposition period was observed on chickpea Hashem. The gross and net reproductive rates were the highest on chickpea Mansour and lowest on lentil. The intrinsic rate of increase and finite rate of increase were the lowest when C. maculatus was reared on lentil and highest when it was reared on other hosts. The longest and shortest mean generation times were observed on lentil and cowpea 1057, respectively. According to the obtained results, lentil was relatively resistant and the other tested legumes were more susceptible hosts for feeding and population increase of C. maculatus . It is concluded that the resistant host cultivar can be proposed to be incorporated into breeding programs to minimize the economic losses incurred by C. maculatus . Highlights: Developmental time of C. maculatus was the longest on lentil. Gross and net reproductive rates were the highest on chickpea Mansour. Intrinsic rate of increase was the lowest when C. maculatus was reared on lentil. Lentil was resistant while other tested legumes were more susceptible to the pest.